2015
DOI: 10.1038/srep16203
|View full text |Cite
|
Sign up to set email alerts
|

Albumin administration prevents neurological damage and death in a mouse model of severe neonatal hyperbilirubinemia

Abstract: Therapies to prevent severe neonatal unconjugated hyperbilirubinemia and kernicterus are phototherapy and, in unresponsive cases, exchange transfusion, which has significant morbidity and mortality risks. Neurotoxicity is caused by the fraction of unconjugated bilirubin not bound to albumin (free bilirubin, Bf). Human serum albumin (HSA) administration was suggested to increase plasma bilirubin-binding capacity. However, its clinical use is infrequent due to difficulties to address its potential preventive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Blood was obtained from anesthetized mice by facial vein bleeding. Bilirubin and albumin were determined in plasma as described previously (29,60).…”
Section: Bilirubin and Albumin Determination In Plasmamentioning
confidence: 99%
“…Blood was obtained from anesthetized mice by facial vein bleeding. Bilirubin and albumin were determined in plasma as described previously (29,60).…”
Section: Bilirubin and Albumin Determination In Plasmamentioning
confidence: 99%
“…Most studies on mouse neonatal jaundice have been performed on genetically modified animals showing impaired bilirubin conjugation and hyperbilirubinemia, which consequently experience early neonatal lethality due to bilirubin toxicity 15 . Here, our aim was to explore the role of the kidneys in iron handling during naturally occurring neonatal jaundice in mice.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the free fraction of unbound bilirubin (Bf) causes neurotoxicity in vivo, and that the decrease of Bf by albumin supplementation increases neuro-protection and survival of the mutant mice and rats [9, 10]. …”
Section: Introductionmentioning
confidence: 99%